Tympanoplasty with and without mastoidectomy in wet ears: a comparative study - Munjal, Manish; Talwar, Gopika; Munjal, Shubham; Saggar, Tulika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Effect of cortical mastoidectomy on graft uptake and graft mobility and thence shift of hearing thresholds was analysed in tympanoplasty in discharging ears. Methods: In this study, 60 subjects of safe chronic suppurative otitis media were selected from the outpatient clinics of Dayanand Medical College and Hospital, Ludhiana. All were subjected to tympanoplasty utilizing the underlay technique. Mastoid exploration was undertaken in the ears with persistent ear discharge. Results: Cortical mastoidectomy performed in 20 (33.3%) out of 60 patients and most of cases were done in superiorly based/superior cuff tympanoplasty group in our study. No statistically significance found between cortical mastoidectomy and different flap technique. Mean hearing gain is more with cortical mastoidectomy (16.85 dB) than without cortical mastoidectomy (13.05 dB) and graft uptake was 97.5% without cortical and 95% with cortical mastoidectomy. Conclusions: There was higher mean gain in thresholds of hearing in subjects with cortical mastoidectomy with tympanoplasty though uptake was almost equal to those without mastoidectomy.